Procedure for studying the repeated contacts and separations in an axial impact involving a non-uniform elastic bar. (September 2016) - Zhao, Yifei; Sun, Zhili; Yu, Zhenliang
Highlights: We establish the impact equation by considering the boundary conditions. A procedure is developed to predict the parameters throughout the changing-status process, by specifying the contact and separation conditions. The behavior of repeated separations and contacts in an axial impact is revealed. Abstract: The generation of different waveforms by axial impacts involving a non-uniform bar can be applied in percussive drilling to increase wave energy transfer. It is a good method for obtaining the force and velocity histories at the impacted ends by introducing a delta function, based on 1-D theory. However, they could not be directly predicted, considering that the two impacted ends may be separated from one another, and a clearance is therefore generated between them. In addition, the changing-status of the non-linearities given the repeated separations and contacts is discussed in this paper. The conditions of separation and contact are provided to present a procedure for predicting the parameters at the impacted ends throughout the non-linear process, and the boundary conditions are also considered. As illustrated in an example impact model, the self-recontact behavior resulting from the wave motion occurs, and the possibility for repeated contacts and separations phenomenon is revealed.